A Current Activated on Depletion of Intracellular Ca(2+) Stores Can Regulate Exocytosis in Adrenal Chromaffin Cells - Fomina, Alla F. (J Neurosci, 1999)
Exocytosis in excitable cells is strongly coupled to Ca(2+) entry through voltage-gated channels but can be evoked by activation of membrane receptors that release Ca(2+) from inositol 1,4,5-trisphosphate-sensitive internal stores. In many cell types, depletion of Ca(2+) stores activates Ca(2+) influx across the plasma membrane, a process known as capacitative or store-operated Ca(2+) entry. This influx is mediated by a number of voltage-independent, Ca(2+)-selective currents. In addition to replenishing Ca(2+) stores, these currents are hypothesized to play an important role in agonist-evoked secretion in nonexcitable cells, although this has not been confirmed experimentally. The existence and physiological function of such currents in excitable cells is not known. Using the capacitance detection technique to monitor exocytosis, we provide direct experimental evidence that a similar mechanism exists in bovine adrenal chromaffin cells. Depletion of intracellular Ca(2+)stores with thapsigargin, a SERCA pump inhibitor, or with BAPTA, an exogenous Ca(2+) chelator, activates a small-amplitude, voltage-independent current that is carried by Ca(2+) and Na(+) ions. Ca(2+) entry through this pathway is sufficient to stimulate exocytosis at negative membrane potentials. In addition, depolarization-evoked exocytosis is markedly facilitated on activation of the current. These data suggest that excitable cells possess a store-operated Ca(2+) influx mechanism that may both directly trigger exocytosis and modulate excitation–secretion coupling.